Aid Effectiveness for Environmental Sustainability (Springer Singapore, 2018)
This collection examines the role that foreign aid can play in dealing with the severe global challenge of climate change, one of the most pressing international development issues of the 21st century. Addressing the key threats of rising temperatures, changes in precipitation, coastal erosion and natural disasters, the book considers the implications for policy and future research, particularly in developing countries. Focusing on the worth of foreign aid in ensuring environmental sustainability, this collection consider how it can be used to improve access to sustainable energy, to promote efficient use of energy resources, to improve emission reduction and support the preservation of biodiversity in forests. Advancing our knowledge about foreign aid and climate change, it provides policy recommendations for the donors and recipient country governments. A cutting edge text on one of the most pressing international development issues of this century, this is key reading for all scholars of international development and climate change.